DisAbling Women and Girls in Austere Times - Stienstra, Deborah (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
During the waves of neoliberal governments in the global North, disabled women and men have been greatly affected by austerity measures. Drawing on feminist disability theory and recent discussions of debility, I argue that neoliberalism and its austerity practices are evident in recent Canadian policies. In particular, feminist analysis of fitting/misfitting, debility, and capacity help us to understand the particular impacts on women with disabilities of these policy changes. In addition, building on Wendy Brown’s (2016) concept of sacrificial citizenship under neoliberalism, I illustrate the pervasive neoliberal tendencies at work in ongoing Canadian discussions of physician-assisted dying. These challenge and extend our understandings of the interplay between gender and disability in austere times.